PENYULUHAN KESEHATAN MELALUI MEDIA VIDEO BERBASIS KEARIFAN LOKAL TERHADAP PENGETAHUAN IBU HAMIL TENTANG PENYAKIT HEPATITIS B : Health Counseling Through Video Media Based On Local Wisdom On Pregnant Women's Knowledge About Hepatitis B Disease - Romauli, Suryati (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2023)
Hepatitis B is a problem that is often found in the care of pregnant women and newborns. Prevention of hepatitis B during pregnancy requires a comprehensive understanding of the disease, namely by providing health counseling through video media based on local wisdom.  Aims to see how this counseling affects pregnant women's understanding of hepatitis B.  Using quasi-experimental forms with two-group pretest-posttest design.  There are 81 pregnant women registered at the Ilekma Health Center.  Simple random sampling was used to select 44 respondents, which were divided into two groups, namely intervention group that received this health counseling, and the control group that did not receive the intervention. Research instruments in the form of questionnaires, the data are analyzed using independent sample t-tests.  Results: Before the intervention, the average score of knowledge of pregnant women based on pre-test findings was 6.41 (intervention group) and 7.50 (control group). The average post-test results after health counseling were 10.77 in the intervention group and 7.45 in the control group. The results of the independent sample t-test showed a significance value of <0.05 which showed that health counseling through video media based on local wisdom had an impact on pregnant women's knowledge about hepatitis B disease.